Unusual synergetic effect of nickel single atoms on the electrocatalytic activity of palladium for alcohol oxidation reactions in alkaline media - Nitaya, T.; Cheng, Yi; Lu, S.; Poochinda, K.; Pruksathorn, K.; Jiang, San Ping (The Royal Society of Chemistry, 2018)
Palladium nanoparticles (Pd NPs) supported on Ni single atoms encapsulated in carbon nanotubes (NiSA) show a significantly enhanced electrocatalytic activity for the oxidation reactions of methanol, ethanol and glycerol in alkaline media due to an unusual electron withdrawal effect of NiSA on Pd NPs.